Blocking effect of fullerene nanoparticles (nC60) on the plant cell structure and its phytotoxicity. (September 2021) - He, Anfei; Jiang, Jing; Ding, Jing; Sheng, G. Daniel
Abstract: Blockage of nanoparticles on plant pore structures might produce phytotoxicity and affect plant uptake indirectly. This study examined the blocking and phytotoxic effects of fullerene nanoparticles (nC60 ) on plants at the cellular level. The malondialdehyde content in plant was normal during nC60 exposure, implying that nC60 caused no acute phytotoxicity, while the normalized relative transpiration significantly decreased, showing that the pore structure of roots was seriously blocked by nC60 . High power optical microscopy and transmission electron microscope showed that root endothelial cells were squeezed, and inner wall structures were damaged by the extrusion of nanoparticles. Low nC60 concentrations inhibited root uptake of lindane, whereas high nC60 concentrations promoted root uptake of lindane, indicating that serious pore blocking by nC60 damaged root cell structure and hence ready transport of lindane from roots to shoots. Significant alterations of fatty acid (FA) saturation degree of root cell membrane indicated that nC60 led to phytotoxicity in the root cell membrane after long-term exposure and nC60 produced phytotoxicity in the process of blocking root pore structures and interfering with cell membrane fluidity. Moreover, the plant cell structures under phytotoxicity were more likely to be damaged mechanically by the extrusion of nanoparticles. These findings may be helpful to better understand the transport pathways of nanoparticles in plants, the phytotoxicity of nanoparticles and the potential risks of nanomaterials used in agriculture. Graphical abstract: Image 1 Highlights: nC60 blocked pore structure of plant roots with no acute phytotoxicity. Pore blocking damaged cell structure forming a new pathway for root uptake. Plant cell structure under phytotoxicity was readily damaged by nC60 extrusion.